1997
DOI: 10.1111/j.1911-3846.1997.tb00545.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Moral Development within Public Accounting by Gender, Staff Level, and Firm*

Abstract: This study extends prior resecirch on the average level of moral development in public accounting by examining five large accounting firms and three staff levels. The research is important because it highlights the need to include auditors from several firms in research designs, provides evidence of differences in moral development among public accounting firms, and profiles the professions' average level of moral development for three levels. The data are from 494 managers and seniors (204 females and 290 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(193 citation statements)
references
References 11 publications
8
183
0
2
Order By: Relevance
“…Finally, prior studies also found women to be more likely to adopt a strict ethical stance (Weeks et al, 1999) and exhibit ethical behavior in the workplace (Bernardi and Arnold, 1997;Lund, 2008). They may also be more likely to behave honestly to teach their children appropriate values (Gottfredson and Hirschi, 1990).…”
Section: H1mentioning
confidence: 99%
“…Finally, prior studies also found women to be more likely to adopt a strict ethical stance (Weeks et al, 1999) and exhibit ethical behavior in the workplace (Bernardi and Arnold, 1997;Lund, 2008). They may also be more likely to behave honestly to teach their children appropriate values (Gottfredson and Hirschi, 1990).…”
Section: H1mentioning
confidence: 99%
“…Females are more likely than males to adopt a strict ethical stance (Weeks et al 1999), exhibit ethical behavior in the workplace (Bernardi and Arnold 1997;Lund 2008;SimgaMugan et al 2005;Valentine and Rittenburg 2004), speak out against unethical behavior (Miethe and Rothschild 1994;Vermeir and Van Kenhove 2008), and become internal whistle blowers (Rothschild and Miethe 1999).…”
Section: More Ethicalmentioning
confidence: 99%
“…Eynon et al (1997), Khazanchi (1995) and Ruegger and King (1992) have found that women are more ethical in a business context. Bernardi and Arnold (1997) and Betz et al (1989) have found that women are less likely to engage in unethical behavior in the work place to gain financial rewards.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%